The Institutional Form of Policyholder Protection Scheme in Indonesia (A Comparison Study Between Indonesia, Malaysia, and South Korea) - Putri Nurul Hidayati (Jurnal Hukum Volkgeist, 2021)
This study is about the urgency of establishing a Policyholder Protection Fund for policyholders and insurance companies in Indonesia. The discussion in this study includes the urgency of establishing a Policyholder Protection Fund in Indonesia, the comparison study between Indonesia, Malaysia and South Korea Policyholder Protection Funds that can be applied in Indonesia. The research method used is a normative juridical research method. The author concludes that the Policyholder Protection Fund in Indonesia should immediately be established. This is because many insurance companies have failed to pay and the Policyholder Protection Fund can provide benefits to policyholders in the form of legal protection. The Policyholder Protection Fund can also provide benefits to the economic system in general. Also, the form of the policyholder guarantee program that can be applied in Indonesia is as an independent institution that is separate from the Deposit Insurance Corporation.